Modern economic prerequisites of development of the knowledge-intensive and high technology productions in Russia taking into account world tendencies - E. Belokonov (Publishing House of the State University of Management, 2016)
Relevance of development of the knowledge-intensive and high technology productions in Russia is proved and the structure of the Russian and world export of high-technology products is analyzed and competitive line items of Russia in high-technology sectors are determined. The most competitive directions of commodity export of high-tech industries are given and measures of support of development of high technology productions are created.